2021
DOI: 10.21203/rs.3.rs-820786/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Untangling Neurodevelopmental Disorders in the Adulthood: A Movement Disorder is the Clue.

Abstract: BackgroundThe genetic landscape of neurodevelopmental disorders is constantly expanding and children with early-onset neurological phenotypes increasingly receive a genetic diagnosis. Nonetheless, the awareness of the chronic course of these conditions, and consequently their recognition and management in the adult population, is still limited. ResultsHerein, we describe four patients with rare neurodevelopmental disorders (SON, ZMYND11, DNMT1 and YY1-related diseases), who received a genetic allocation only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Therefore, for the purpose of this study, 50-day old (pre-symptomatic) and 100-day old animals (post-symptomatic) were classified into respective groups, to represent stages of the disease. Among the aberrantly spliced genes, zinc finger, MYND typecontaining 11 ( Zmynd11 ) is of particular interest due to its recent implications in autism-related motor delay (Moskowitz, Belnap et al 2016); intellectual disability (Pruccoli, Graziano et al 2021) and brain atrophy and ataxia (Indelicato, Zech et al 2022). In addition, Zmynd11/ZMYND11 has been previously reported to be an RNA binding partner of TDP-43 in the mouse brain (Narayanan, Mangelsdorf et al 2013), rat cortical neurons (Sephton, Cenik et al 2010) and post-mortem human brain (Tollervey, Curk et al 2011) and was reported to be aberrantly spliced in the spinal cord of sporadic ALS patients with TDP-43 pathology (Rabin, Kim et al 2010).…”
Section: Descriptionmentioning
confidence: 99%
“…Therefore, for the purpose of this study, 50-day old (pre-symptomatic) and 100-day old animals (post-symptomatic) were classified into respective groups, to represent stages of the disease. Among the aberrantly spliced genes, zinc finger, MYND typecontaining 11 ( Zmynd11 ) is of particular interest due to its recent implications in autism-related motor delay (Moskowitz, Belnap et al 2016); intellectual disability (Pruccoli, Graziano et al 2021) and brain atrophy and ataxia (Indelicato, Zech et al 2022). In addition, Zmynd11/ZMYND11 has been previously reported to be an RNA binding partner of TDP-43 in the mouse brain (Narayanan, Mangelsdorf et al 2013), rat cortical neurons (Sephton, Cenik et al 2010) and post-mortem human brain (Tollervey, Curk et al 2011) and was reported to be aberrantly spliced in the spinal cord of sporadic ALS patients with TDP-43 pathology (Rabin, Kim et al 2010).…”
Section: Descriptionmentioning
confidence: 99%